Cellular-to-Dendritic and Dendritic-to-Cellular Morphological Transitions in a Ternary Al-Mg-Si Alloy - Brito, C. [UNESP]; Nguyen-Thi, H.; Mangelinck-Noël, N.; Cheung, N.; Spinelli, J. E.; Garcia, A. (IOP Publishing, 2019)
The study is focused on the influence of solidification thermal parameters upon the evolution of the microstructure (either cells or dendrites) of an Al-3wt%Mg-1wt%Si ternary alloy. It is well known that the application properties of metallic alloys will greatly depend on the final morphology of the microstructure. As a consequence, various studies have been carried out in order to determine the ranges of cooling rates associated with dendritic-cellular transitions in multicomponent alloys. In the present research work, directional solidification experiments were conducted using either a Bridgman (steady-state) device or another device that allows the solidification under transient conditions (unsteady-state). Thus, a broad range of cooling rates (), varying from 0.003K/s to 40K/s could be achieved. This led to the identification of a complete series of cellular/dendritic/cellular transitions. For low cooling rate experiments, low cooling rate cells to dendrites transition happens. Moreover, at a high cooling rate, a novel transition from dendrites to high cooling rate cells could be observed for the Al-3wt%Mg-1wt%Si alloy. Additionally, cell spacing λC and primary dendritic spacing λ1 are related to the cooling rate by power function growth laws characterized by the same exponent (-0.55) for both steady-state and unsteady-state solidification conditions.